Application and effect of negative pressure chambers on pipeline explosion venting. (May 2016) - Shao, Hao; Jiang, Shuguang; Wu, Zhengyan; Zhang, Weiqing; Wang, Kai
Abstract: Explosion venting is a frequently-used way to lower explosion pressure and accident loss. Recently, studies of vessel explosion venting have received much attention, while little attention has been paid to pipe explosion venting. This study researched the characteristics of explosion venting for Coal Bed Methane (CBM) transfer pipe, and proposed the way of explosion venting to chamber in order to avoid the influence of explosion venting on external environment, and investigated the effects of explosion venting to atmosphere and chamber. When explosion venting to atmosphere, the average explosion impulse 4.89 kPa s; when explosion venting to 0 MPa (atmospheric pressure) chamber, average explosion impulse is 7.52 kPa s; when explosion venting to −0.01 MPa chamber, explosion flame and pressure obviously drop, and average explosion impulse decreases to 4.08 kPa s; when explosion venting to −0.09 MPa chamber, explosion flame goes out and average explosion impulse is 1.45 kPa s. Thus, the effect of explosion venting to negative chamber is far better than that to atmospheric chamber. Negative chamber can absorb more explosion gas and energy, increase stretch of explosion flame, and eliminate free radical of gas explosion. All these can promote the effect of explosion venting to negative chamber. Highlights: Way of explosion venting to chamber was proposed. Explosion venting to chamber can avoid influencing external environment. Effect of explosion venting to chamber becomes better as the pressure in chamber lowers. Negative chamber can absorb more explosion gas and energy then atmospheric pressure one.